KONTRIBUSI PENGASUH DI PANTI ASUHAN MUSLIMIN DALAM PEMENUHANDIMENSI EMOSIONAL WARMTH BERDASARKAN KERANGKA PERLINDUNGANDAN KESEJAHTERAAN SOSIAL ANAK - Rahmadiana, Fatiyah; Sekar, Dwi Amalia Chandra (UI Scholars Hub, 2019)
This study aims to provide an overview of the caregiver's contribution in fulfilling child welfare in orphanages as a substitute for parents who are needed to fulfill children's development needs. This study uses the UNICEF Child Welfare and Protection Framework, namely Parenting Capacity and limits the discussion on one of the indicators, namely Emotional Warmth. This study uses a qualitative approach with a type of descriptive research. Data collection methods used are literature studies, observations and in-depth interviews. The results of this study illustrate the efforts of caregivers in fulfilling emotional warmth by showing their affection first getting closer to foster children by inviting children to talk about their daily lives, hugging children in response to hugs given by children first, listen when the children tell what they are feeling, show sensitivity to the child's condition such as when the child is alone or crying, teach independence by involving children in daily activities in the orphanage which are the duty of foster children. With the fulfillment of the emotional warmth of caregivers showing one of the parenting capacities that contribute to the welfare of foster children in the orphanage. Some of the things that support the process of fulfilling emotional warmth at the institution are, the caregiver's understanding of his work and the provisions of institutions that support caregivers to carry out their roles optimally. Several inhibiting factors were found, namely, caregivers who had other responsibilities outside the institution so that they could not always carry out their roles as caregivers in the institution, there were differences of opinion between caregivers regarding the care process, and there were no written regulations requiring caregivers to accompany children's daily lives The conclusion of this study is that caregivers strive to fulfill emotional warmth in the care process at the institution, by not only paying attention to the physical needs of the child but also paying attention to the emotional needs of the child.